2016
DOI: 10.1039/c6pp00264a
|View full text |Cite
|
Sign up to set email alerts
|

Switch of the magnetic field effect on photon upconversion based on sensitized triplet-triplet annihilation

Abstract: Magnetic field effects (MFEs) on photon upconversion based on sensitized triplet-triplet annihilation (TTA-UC) are examined in platinum(ii) octaethylporphyrin/9,10-diphenylanthracene (DPA) systems at different DPA concentrations and laser power densities. Positive MFEs on TTA-UC are observed for the first time and are most likely attributable to aggregation of DPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 38 publications
1
19
1
Order By: Relevance
“…The magnetic field effect (MFE %) is defined as MFE % = (( I – I 0 )/ I 0 ) × 100%, where I and I 0 are the integrated upconverted emission intensities in the presence and absence of magnetic field, respectively. The MFE % for DPA reaches about −2.0% at 326 mT, which is similar to previous reports. , For the dimers, the MFE % reaches approximately −2.8, −3.2, and −2.6% for o-, m-, and p-dimer, respectively.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The magnetic field effect (MFE %) is defined as MFE % = (( I – I 0 )/ I 0 ) × 100%, where I and I 0 are the integrated upconverted emission intensities in the presence and absence of magnetic field, respectively. The MFE % for DPA reaches about −2.0% at 326 mT, which is similar to previous reports. , For the dimers, the MFE % reaches approximately −2.8, −3.2, and −2.6% for o-, m-, and p-dimer, respectively.…”
Section: Results and Discussionsupporting
confidence: 91%
“…The MFE % for DPA reaches about −2.0% at 326 mT, which is similar to previous reports. 35,39 For the dimers, the MFE % reaches approximately −2.8, −3.2, and −2.6% for o-, m-, and p-dimer, respectively.…”
Section: ■ Introductionmentioning
confidence: 98%
“…[28] While less frequently employed, several studies have confirmed this effect across multiple annihilators and further validate a bimolecular triplet quenching mechanism. [29,30]…”
Section: Introductionmentioning
confidence: 99%
“…3,8,18−26 However, it is not clear whether T-channel TTA takes place in DPA molecules. 6,15,20,21,27 It is known that the intensity of delayed fluorescence produced by TTA can be modulated by the application of an external magnetic field, 2,28 and TTA processes have been studied with magnetic fields in solid states 2,29−33 and in solutions. 19,21,34−38 The effects of a magnetic field on the delayed fluorescence in crystalline DPA were first reported in the 1970s, with three peaks of fluorescence intensity observed when a magnetic field of 0.5−2.5 T was applied; 2 however, the origin of these peaks has not yet been clarified.…”
mentioning
confidence: 99%